Allergic disease and keratoconus: A two-sample univariable and multivariable Mendelian randomization study - Hanlu Xu; Yajing Wen; Huikang Zheng; Dan Jiang; Wei Chen (World Allergy Organization Journal, 2024)
Background: There is accumulating evidence that allergy is a risk factor for keratoconus. Nonetheless the association between allergic disease and keratoconus remains controversial. We performed a two-sample Mendelian randomization (MR) study to determine the putative causal association of 4 allergic diseases (allergic conjunctivitis, allergic asthma, allergic rhinitis and atopic dermatitis) with keratoconus. Methods: Summary statistics were obtained from genome-wide association studies (GWAS) of allergic conjunctivitis (AC) (20,958 cases and 356,319 controls), allergic asthma (AA) (9631 cases and 210,122 controls), allergic rhinitis (AR) (11,009 cases and 359,149 controls), atopic dermatitis (AD) (13,473 cases and 336,589 controls), keratoconus (KC) (2116 cases and 24,626 controls) and 91 circulating inflammatory cytokines (n = 14,824). Two-sample univariable and multivariable MR analyses were performed. A two-step MR was then applied to determine whether systemic inflammatory cytokines mediated the effect of allergic disease on keratoconus. Results: The causal odds ratio (OR) estimate of genetically determined KC was 1.66 (95% CI: 1.32–2.08; P < 0.001) for AC, 1.29 (95% CI: 1.10–1.51, P = 0.0014) for AA, 1.39 (95% CI: 1.15–1.68; P < 0.001) for AR and 1.30 (95% CI: 1.17–1.45, P < 0.001) for AD. Multivariable MR indicated a suggestive association between AC and KC after conditioning on other allergic diseases (OR 1.61; 95% CI: 1.10–2.34; P adjusted = 0.054). Two-step MR revealed that the effect was not mediated by systemic inflammatory cytokines. Conclusions: Our findings provide evidence of a potential causal relationship between AC and KC. The effect of AC on KC may be mediated via other systemic inflammatory cytokines not included in the present study, or by alternative mechanisms. These findings may offer insight for prevention and intervention strategies to lower the risk of KC in patients with AC.